Shared meditation involving cancer patients, health professionals and third persons is relevant and improves well-being: IMPLIC pilot study - Virginie Prevost; Sophie Lefevre-Arbogast; Alexandra Leconte; Claire Delorme; Sandrine Benoit; Titi Tran; Bénédicte Clarisse (BMC, 2022)
Abstract Background Alleviating suffering and improving quality of life are universally shared goals. In this context, we implemented a pilot study to assess the feasibility and acceptability of a mindfulness intervention in the form of meditation involving together cancer patients, health professionals, and third persons. Methods Two groups of 15 participants equally composed of patients, health professionals and third persons were constituted. A dedicated programme on mindfulness and compassion was constructed, including 12 weekly sessions of 1.5 h and a half-day retreat. Adherence and satisfaction with the programme were evaluated. All participants completed questionnaires on perceived stress, quality of life, mindfulness, empathy, and self-efficacy. Burnout was assessed in health professionals. Results Shared meditation was feasible as 70% of participants attended ≥ 80% of the 13 meditation sessions. Satisfaction with the programme was high (median satisfaction score: 9.1 out of 10) and all participants expressed positive attitudes towards shared meditation and a benefit on their global quality of life. Participants reported significant improvement in stress (p < 0.001), global quality of life (p = 0.004), self-efficacy (p < 0.001), and mindfulness skills (p < 0.001) from baseline to post-programme. Conclusions This study demonstrated the feasibility of a shared dedicated meditation programme in terms of participation and acceptability of participants. The measured benefits observed among participants furthermore justify the interest of a subsequent randomized study aiming to demonstrate the potential added value of shared meditation by promoting bridge-building between cancer patients, health professionals and others. Trial Registration ClinicalTrials.gov. NCT04410185 . Registered on June 1, 2020.